Design and Build Grill and Retort Basket Design Based on Autodesk Inventor Software at PT Banyuwangi Cannery Indonesia - Iin Kurniawati; Muhammad Faizul Mukarom; Nur Wahyudi; Rifki Zainur Rahman; Sunaryanto Sunaryanto (G-Tech: Jurnal Teknologi Terapan, 2024)
PT Banyuwangi Canenery Indonesia, which is based in Banyuwangi, Indonesia, has been growing and winning over a lot of clients. Up till now, the canning sector has developed and updated its infrastructure. Grills and retort baskets were erected in the gutters by PT Banyuwangi Canenery Indonesia. R&D is a term used to describe one approach to research and development.Research-related instruments used in the R&D technique include basket retorts based on Autodesk Inventor software and grill and response tests. The simulation results show that the retort basket experiences stress of 118.6 mpa to 160.2 mpa, displacement of 0.02 mm to 33.88 mm, strain of 0.002332 ul to -0.002339 ul, and a safety factor of 15 ul to 1.86 ul. While grill experienced stress of 7.302 to -6.241 mpa, displacement of 0.0159 mm to 0.03085 mm, strain of 4.733e-05 ul to -5.508e-05 ul, and safety factor of 15 ul.